Pinterest Homemade Sunscreens: A Recipe for Sunburn. Issue 9 (28th July 2020) - Merten, Julie Williams; Roberts, Kristi J.; King, Jessica L.; McKenzie, Lara B.
ABSTRACT: Social media, specifically Pinterest with more than 175 million users, has changed the way people seek and share health information. Recent consumer interest in natural products has led to an increase of shared recipes for homemade products including sunscreen. Homemade sunscreen products are risky because they are not regulated or tested for efficacy like commercial sunscreens. With rising skin cancer rates, the use of effective broadband sunscreen is critical to reduce incidence of skin cancer. This study used directed content analysis to examine how homemade sunscreens were portrayed on Pinterest. Using the search terms, homemade sunscreen and natural sunscreen, researchers sampled every fifth pin to collect 189 relevant pins. A codebook was developed, pilot tested, and used to code pins. Two researchers coded pins and interrater reliability was established at 90%. Of the 189 pins, the majority of pins (95.2%) positively portrayed the effectiveness of homemade sunscreens and 68.3% recommended recipes for homemade sunscreens that offered insufficient UV radiation protection. Sun Protection Factor (SPF) claims were made in 33.3% of pins with a range of SPF 2 to SPF 50. In this sample of pins, 41.8% of pins had been saved by other users ranging from one to more than 21, 000 times. Social media is a powerful source of health information. However, this study revealed widespread interest and acceptance of insufficient sun protection information. Pinterest and the interest in homemade recipes for sunscreen present an opportunity for public health professionals to proactively engage on social media. Abbreviations: US: United States; SPF: sun protection factor; USFDA: United states food and drug administration; UV: ultraviolet